Memoirs of a Goldfish - Scillian, Devin; Bowers, Tim (Ann Arbor, MI : Sleeping Bear Press, 2010)
A goldfish gives a personal account of his experiences while swimming around his bowl as it slowly fills with fish and other accessories, only to realize when he is relocated for a cleaning how much he misses them.
Keywords: Goldfish -- Fiction; Friendship -- Fiction